PENGARUH KOMPENSASI, KEADILAN PROSEDURAL DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA KARYAWAN PD BPR BKK PURBALINGGA - Nurul Hidayat Umar; Heri Setiawan; Endang Sri W (Majalah Imiah Manajemen & Bisnis, 2020)
This research entitled "The Effect of Compensation, Procedural Justice and Physical Work Environment on PD BPR BKK Purbalingga Employee Job Satisfaction". The purpose of this study was to analyze the significance of the effect of compensation on job satisfaction of PD BPR BKK Purbalingga employees, to analyze the significance of procedural justice on job satisfaction of PD BPR BKK Purbalingga employees and to analyze the significance of physical work environment on PD BPR BKK Purbalingga employee job satisfaction. The analysis uses multiple linear regression. From this research it can be concluded: The hypothesis which states compensation has a significant effect on job satisfaction of PD BPR BKK Purbalingga employees, with a 95% confidence rate, accepted. This is evidenced by the t test which proves that the t count compensation is greater than t table (2,410> 2,0025). The hypothesis that procedural justice has a significant effect on job satisfaction of PD BPR BKK Purbalingga employees, with a 95% confidence rate, is accepted. This is evidenced by the t test which proves that procedural fairness is greater than t table (2,941> 2,0025). The hypothesis that the physical work environment has a significant effect on job satisfaction of PD BPR BKK Purbalingga employees, with a 95% confidence score, is accepted. This is evidenced by the t test which proves that t counts the physical work environment is greater than t table (4.982> 2.0025).